2005
DOI: 10.1302/0301-620x.87b1.15249
|View full text |Cite
|
Sign up to set email alerts
|

Pertrochanteric femoral fractures treated with a dynamic hip screw or a proximal femoral nail

Abstract: We treated 108 patients with a pertrochanteric femoral fracture using either the dynamic hip screw or the proximal femoral nail in this prospective, randomised series. We compared walking ability before fracture, intra-operative variables and return to their residence. Patients treated with the proximal femoral nail (n = 42) had regained their pre-operative walking ability significantly (p = 0.04) more often by the four-month review than those treated with the dynamic hip screw (n = 41). Peri-operative or imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
174
4
17

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(220 citation statements)
references
References 22 publications
25
174
4
17
Order By: Relevance
“…Using American Board of Orthopaedic Surgery (ABOS) Part II data, Anglen and Weinstein reported that use of IM fixation increased from 3% in 1999 to 67% of cases in 2006 [3]. Numerous studies have been published comparing sliding compression hip screw and side plate with IM fixation [2,12,16,17,29,31,32]. However, results have been contradictory in terms of outcomes [2,12,16,17,29,31,32] with the only consistent differences reported between the two fixation techniques being increased complications (particularly intraoperative and postoperative fractures) and a higher reoperation rate with IMN [4,10,16,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using American Board of Orthopaedic Surgery (ABOS) Part II data, Anglen and Weinstein reported that use of IM fixation increased from 3% in 1999 to 67% of cases in 2006 [3]. Numerous studies have been published comparing sliding compression hip screw and side plate with IM fixation [2,12,16,17,29,31,32]. However, results have been contradictory in terms of outcomes [2,12,16,17,29,31,32] with the only consistent differences reported between the two fixation techniques being increased complications (particularly intraoperative and postoperative fractures) and a higher reoperation rate with IMN [4,10,16,29].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, a sliding hip screw (SHS) has been the preferred implant to stabilize these fractures [5,13,18,21,24,25,35]. However, intramedullary hip screw devices have gained popularity for stabilizing this fracture type [2,4,7,8,10,12,16,17,29,31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autores são de opinião que a haste PFN ® possibilita a obtenção de excelentes resultados no tratamento da fratura trocantérica instável do fêmur, principalmente quanto à estabilidade propiciada pelo implante, que permite deambulação precoce com melhor reabilitação funcional do paciente idoso e alto índice de consolidação decorrente da preservação do envelope de partes moles em torno da fratura (37)(38)(39)(40) .…”
Section: Discussionunclassified
“…The PFN group consistently required shorter incisions (p=0.0001), had less blood loss and shorter operative times (p=0.0001) when compared to the DHS group. Baumgaertner et al 6 had comparable results regarding length of incision and blood loss similar to Pajarinen et al 7 and Ishrat A Khan et al 8 The operative times on the other hand were reported to be comparable in the studies of Ishrat A Khan et al 8 and Saudan et al 9 Pan et al 10 and Giraud et al 11 reported significantly less surgery times for the PFN group compared to the DHS group. Papasimos et al 12 had reported shorted surgery times for the DHS group compared to the PFN group.…”
Section: Resultsmentioning
confidence: 58%